Assessing the Effects of Tourist Provisioning on the Health of Wild Barbary Macaques in Morocco. - Laëtitia Maréchal; Stuart Semple; Bonaventura Majolo; Ann MacLarnon (PLoS ONE, 2016)
Feeding wildlife is a very popular tourist activity, largely because it facilitates the close observation of animals in their natural habitat. Such provisioning may benefit animals by improving their survival and reproductive success, especially during periods of natural food shortage. However, provisioning by tourists may also have negative impacts on the health of the animals involved; to date such impacts are poorly understood. Here, we investigated the effects of tourist provisioning on the health of wild adult Barbary macaques, Macaca sylvanus, in Morocco. We compared health measures between a heavily provisioned group and a group that received negligible food from tourists and, in the former group, we also assessed health measures in relation to the intensity of provisioning. We used a broad range of non-invasive health measures relating to birth rate and survival, disease and injury risk, body size and condition, and physiological stress. Our findings indicate that feeding by tourists may overall have negative impacts on the health of Barbary macaques, being linked in particular to larger body size, elevated stress levels and more alopecia. Finally, we propose a framework to help consider the potential costs and benefits of provisioning, which may facilitate future research and management decisions on whether-and how much-provisioning is acceptable.